THE DOCUMENTS OF THE LITHUANIAN COMMUNITIES IN THE USA OF THE END OF 19th CENTURY–BEGINNING OF THE 20th CENTURY: WRITTEN MEMORY - STEPONAITIENĖ, JOLITA (Knygotyra, 2015)
Lietuvos nacionalinė Martyno Mažvydo biblioteka,Gedimino pr. 51, LT-01504 Vilnius, LietuvaEl. paštas: j.steponaitiene@lnb.ltAt the end of the 19th century the first surge of Lithuanian immigrants flowed to the United States of America. Economical and political reasons forced Lithuanians to look for a “better life” in the strange country which could give a possibility to earn for substantial meal, better shelter, to pray in native language and cluster in fellow clubs. Settling in the free country, Lithuanians undertook active public and cultural activity, associated in societies, issued newspapers and published books.The objective of the article is to review the main groups of printed and archival heritage of Lithuanian emigrants of the end of the 19th century – the beginning of the 20th century, and to evaluate significance of the said heritage for Abstractresearch of this period. Special attention is given to manuscript documents preserved in the Rare Books and Manuscripts Department of Martynas Mažvydas National Library of Lithuania. The said documents, cherishing printed and written memory, are important in several aspects: they witness integration of Lithuanians into the life of multinational America, accepting of American terms-words, relation with their own Lithuanian-historical-Christian roots and Lithuania. At the end of the 19th century one fifth of the nation left Lithuania. They created new life for themselves, accepted different experience and living, committed to their being in various ways, even though not all sources, documents could be preserved.
Keywords: ...